2ln(x+4)=4

Simple and best practice solution for 2ln(x+4)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2ln(x+4)=4 equation:


Simplifying
2ln(x + 4) = 4

Reorder the terms:
2ln(4 + x) = 4
(4 * 2ln + x * 2ln) = 4
(8ln + 2lnx) = 4

Solving
8ln + 2lnx = 4

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-4 + 8ln + 2lnx = 4 + -4

Combine like terms: 4 + -4 = 0
-4 + 8ln + 2lnx = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-2 + 4ln + lnx) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-2 + 4ln + lnx)' equal to zero and attempt to solve: Simplifying -2 + 4ln + lnx = 0 Solving -2 + 4ln + lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 4ln + 2 + lnx = 0 + 2 Reorder the terms: -2 + 2 + 4ln + lnx = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 4ln + lnx = 0 + 2 4ln + lnx = 0 + 2 Combine like terms: 0 + 2 = 2 4ln + lnx = 2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -(7-8A)-(2+7A)-27=-(3-7A)+(-A)+2 | | 2(2x-i)-4x-6x= | | 5*3/5x-5*6 | | 9x^4-18x^2+5=0 | | 4r^3=72 | | 1/2x2/7= | | 4c=54 | | 1.3x+2.1=5.7 | | 24+4b=8 | | 17.64*8= | | 7(8)=56 | | 81x^2+1=101 | | a=3*w | | (-7xz^5/y)^3 | | -4(3+4n-3m)= | | -4.5-1.3+4.5= | | Log(x+4)+log(4x+3)=2log(2x) | | 2250/2= | | 14m-3n-2m+5n= | | 10*15*15= | | f=bexp(-a*x) | | x+2y=4y+3 | | -4/7u=-16 | | V=6.5*5.5*16 | | 3w/12-12/5w | | 4a+2b+3a= | | U(v+3)=3 | | 28=-14y | | 2x-y=4y+6 | | 4(u-4)-7u=5 | | -6.1(2s+4)-1.8(3s-5)= | | -9M+13-8(M-5)=6M-(8M-3)-7M+2 |

Equations solver categories